Tunnetiloja mittaavat menetelmät epänormaalin pelon hoidossa - Heidi Annika Martikainen; Erkki Mäkinen (Finnish Social and Health Informatics Association, 2018)
This article surveys methods for measuring emotions. The focus is on emotion identification and measurement from behavior and physiological signals and on the instruments used. We also consider the utilization of the results of these measurements in treating phobias, especially as a supporting tool for cognitive behavioral therapy.